Dampak Pandemi Covid-19 Terhadap Kinerja Lembaga Kemahasiswaan di Universitas Negeri Makassar - Mr. Herianto; Mubarak Dahlan (Rayhan Intermedia, 2023)
This study aims to find out: 1) What are the views of the Management of student organizations at the Faculty of Social Sciences and Law, Makassar State University regarding the Covid-19 Pandemic; 2) What is the impact of Covid-19 on the performance of student organizations at the Faculty of Social Sciences and Law, Makassar State University. This study uses a type of qualitative research. The selected informants are general chairmen or administrators who are considered to be able to provide the information sought by the researcher. Researchers collected data by means of observation, interviews and documentation. This study uses analytical techniques based on the theory of Cultural Adaptation. The results of this study show: 1) Covid-19 is a biological virus that is very dangerous and can claim human life. Apart from being dangerous to health, this virus also greatly impacts the performance of Student Organizations. 2) The Covid-19 virus greatly impacted the performance of Student Institutions at the Faculty of Social Sciences and Law, Makassar State University, many activities were carried out online, organizational communication was hampered, institutional regeneration had decreased, administration was experiencing difficulties, and several work programs were hampered or even not implemented .